The collaboration economy : how to meet business, social, and environmental needs and gain competitive advantage - Lowitt, Eric, 1972- (Jossey-Bass & Pfeiffer Imprints, Wiley, 2013)
How six industries are collaborating with competitors, society, and the public sector for competitive advantage No longer can we consume the equivalent of 1.3 Earths resources and expect to remain prosperous in perpetuity. We need a new economic paradigm, one that yields growth in a way that strengthens the global systems we rely on daily for survival, such as the global water, food, and energy systems. The Collaboration Economy-a model where the private, public, and civil sectors collaborate for prosperity that can last in perpetuity-is emerging. But what does this economic model lo.